Disentangling the Role of Contract Types and Sector Disparities for Public Service Motivation - Christian Grund; Kirsten Thommes (Institute for the Study of Labor (IZA), 2015)
The intention of "doing good for society" is regarded to be a crucial motivator for employees in the public sector in order for them to perform well. Recent research in the public sector literature calls for a deeper understanding of how this specific public service motivation (PSM) is shaped. In our paper, we analyze how different degrees of inclusion in the public sector impact PSM. We also investigate how prospects of employment relations (fixed-term versus permanent contracts), temporal differences (part-time versus full-time employment), and actual jobs (core versus subsidiary jobs) moderate PSM in public service. Our findings show that aspects of PSM are affected by these employment characteristics in various ways, suggesting that the factors influencing PSM are multifaceted and that actual employment conditions have to be taken into consideration when assessing PSM.
Keywords: M55; J45; H83; 330; job characteristics; motivation; PSM; public sector; part-time; temporary employment